Perselisihan Tasawuf Di Nusantara: Perspektif Teori Konflik Karl Marx - Salapudin, Moh (Indonesian Journal of Islamic Theology and Philosophy, 2023)
Abstract;Islam Nusantara is an Islam that is very strong with nuances of Sufism (Sufism). The process of spreading Sufism in the archipelago turned out to be colored by feuds between the figures. In Java there was a feud between Walisongo and Sheikh Siti Jenar and in the Sultanate of Aceh there was a feud between Nuruddin Ar-Raniri and followers of Hamzah Fansuri and Syamsuddin Sumatrani. This article attempts to explain the feuds and disputes over Sufism in the archipelago using Karl Marx's conflict theory. In this theory, conflicts that occur in society, including the conflict over Sufism in the archipelago, proceed through a dialectical process: thesis, antithesis and synthesis. The conflicts over Sufism in the archipelago, which proceeded in a thesis-antithesis pattern, then produced a synthesis in the form of Islam which, on the one hand, was very strong with nuances of Sufism, but on the other hand did not ignore aspects of the Shari'a or Fiqh, namely tarekat. This article also concludes that the emergence of the concept of Nusantara Islam is a product of the dialectic of conflict over Sufism in the archipelago. At first it was Islam (without frills, as a thesis), but Islam without frills was apparently deemed unable to differentiate between what was Islam and what was Arab custom, so that Islam was considered Arabian Islam (antithesis). Then Islam Nusantara was born (as a synthesis), namely Islam that was not Arabian and accommodating to local values.Keywords:Abdul Qadir al-Jailani; Akhlaqi Sufism; Modernity. Abstrak;Islam Nusantara adalah Islam yang sangat kental dengan nuansa tasawuf (sufisme). Proses penyebaran tasawuf di Nusantara ternyata diwarnai perseteruan-persetruan para tokohnya. Di Jawa terjadi perseteruan antara Walisongo dengan Syekh Siti Jenar dan di Kesultanan Aceh terjadi perseteruan antara Nuruddin Ar-Raniri dengan pengikut Hamzah Fansuri dan Syamsuddin Sumatrani. Artikel ini berupaya menjelaskan perseteruan dan perselisihan tasawuf di Nusantara tersebut menggunakan teori konflik Karl Marx. Dalam teori ini konflik-konflik yang terjadi di masyarakat, termasuk perseteruan tasawuf di Nusantara, berjalan melalui proses dialektika: tesis, antitesis, dan sintesis. Pertentangan-pertentangan tasawuf di Nusantara, yang berjalan dalam pola tesis-antitesis kemudian menghasilkan sintesis berupa Islam yang di satu sisi sangat kental dengan nuansa tasawuf namun di sisi lain tidak mengabaikan aspek syariat atau fikih, yaitu tarekat. Artikel ini juga menyimpulkan bahwa kemunculan konsep Islam Nusantara merupakan produk dialektika perseteruan tasawuf di Nusantara. Pada mulanya Islam (tanpa embel-embel, sebagai tesis), namun Islam yang tanpa embel-embel tersebut ternyata dinilai tidak dapat memilah mana yang Islam dan mana yang adat Arab, sehingga Islam tersebut dianggap Islam kearab-araban (antitesis). Kemudian lahirlah Islam Nusantara (sebagai sintesis), yakni Islam yang tidak kearab-araban dan akomodatif terhadap nilai-nilai lokal.Kata Kunci:   Abdul Qadir al-Jailani; Modernitas; Tasawuf Akhlaqi.